Operasi Plastik Dalam Perspektif Gratitude Orang Kristen: Sebuah Tinjauan Teologis - Yustinus (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2025)
The phenomenon of plastic surgery is increasingly prevalent in contemporary culture, in line with rising beauty standards and social pressure regarding physical appearance. The purpose of this study is to provide a correct and in-depth understanding of God's perspective on the temporary beauty of the human body and to cultivate gratitude in facing personal dissatisfaction. This research employs a qualitative approach using a phenomenological method to explore the meaning of plastic surgery in the context of gratitude. The findings reveal that a lack of gratitude can heighten dissatisfaction with one's body, whereas a deep sense of gratitude can serve as a strong safeguard for individuals against the pressure of worldly beauty standards and help them avoid plastic surgery for the sake of personal satisfaction. This study not only contributes academically to the field of Christian theology and ethics but also offers practical implications in guiding Christians to make decisions that align with their faith in the context of plastic surgery.